DEVELOPMENT OF INSTRUCTIONAL MODEL WITH SIMULATED SITUATIONS TO ENHANCE PERFORMANCE IN EMERGENCY NURSING OF NURSING STUDENTS - Tantalanukul, Seubtrakul; Khiaolueang, Dujduean; Kooariyakul, Ananya; Srijaiwong, Sitanan; Fongkerd, Suriya; Isarangura Na Ayudhaya, Phitinan; Pusopa, Chuleeporn (Journal of Education and Innovation, 2025)
This research and development study aimed to examine the current teaching conditions, develop an instructional model, and evaluate the effectiveness of a simulation-based teaching model to enhance emergency nursing competencies among nursing students. The study was conducted in three phases: 1) A survey of 15 nursing instructors to assess current teaching practices; 2) Development of a teaching model based on phase 1 results and literature review, validated by three experts; and 3) Evaluation of the model's effectiveness using a quasi-experimental design with 60 nursing students (30 each in experimental and control groups). The research findings revealed: 1) Current teaching methods inadequately support the application of theoretical knowledge to emergency nursing practice; 2) The developed teaching model comprises three stages: preparation, implementation, and evaluation; 3) Post-intervention, the experimental group showed significantly higher emergency nursing practice scores compared to their pre-test scores and the control group's scores (p < .05). The study concludes that the developed simulation-based teaching model effectively enhances nursing students' emergency nursing competencies. This model offers a promising approach for bridging the theory-practice gap in nursing education, particularly in emergency care contexts. Further research is recommended to explore the long-term impacts and applicability of this model across various nursing specialties.